The social impact investment race: toward an interpretative framework. Issue 1 (8th January 2018) - Calderini, Mario; Chiodo, Veronica; Michelucci, Fania Valeria
Abstract : Purpose: This paper aims to develop an interpretative framework of the evolution of social impact investment (SII) in different countries. SII is a strategy of asset allocation, which combines financial profitability with a measurable social and environmental impact. Design/methodology/approach: Through a thematic analysis of 75 documents, i.e. reports, experts' considerations, reflections on practitioners' experience, meetings' minutes, written by the SII Taskforce of the Group of Eight and the relative National Advisory Boards, the authors identify the main themes connected to the topic of SII development and recognize four main elements useful to segment the market, namely, information asymmetry, financial instruments, source of capital and market intermediation. Findings: They map the ongoing practices in the Group of Eight's members and distinguish two speeds in the evolution of SII: on one hand, there is a group of roadrunners, which pave the way to SII and in which SII activities have being institutionalized; on the other hand, there is a wider group of chasers, where the SII infrastructures lack any systematization. Originality/value: Although some authors provide preliminary interpretations of the SII evolution, they mainly focus on the national level and do not provide any cross-countries analysis. The findings of the present work contribute to overcome the lack of evidence characterizing the SII field and the absence of comparable and consistent data at the global level by filling the academic literature about SII, through a structured interpretative framework.